Representations of Jesus in Australian Poetry in the 1950s - Watt, Paul (Journal for the academic study of religion, 2022)
Studies of Australian poetry in the 1950s are preoccupied with the form, function and style of the genre. Poetry was regarded as high art cultivated by learned men and women, and published by international publishers such as Oxford University Press. Religious poetry is occasionally represented in these anthologies, but poems of or about Jesus are noticeable by their absence. By contrast, poems about Jesus can be found in newspapers and in self-published or boutique anthologies of religious verse. These personal expressions of faith, outside the sphere of high art, often show both European and Australian imaginings of Jesus. A study of religious verse of the period outside of the canonical literature illustrates the variety of the genre in the 1950s and the significance it held for Australian Christians.